Analisis Pendapatan Usahatani Padi Rawa Pasang Surut di Desa Bentuk Jaya Kecamatan Dadahup Kabupaten Kapuas - Simanjuntak, Radot Martua Pardamean; Maleha; Pordamantra; Shinta, Tri Yuliana Eka (J-SEA (Journal Socio Economic Agricultural), 2026)
Swamp lands have strategic potential to support agricultural sector growth, but tidal swamp rice farming still faces productivity, cost, and income constraints. This study analyzes farming activities, revenue, costs, income, and financial feasibility of tidal swamp rice farming in Bentuk Jaya Village, Dadahup Subdistrict, Kapuas Regency. A descriptive quantitative approach was applied. Thirty active rice farmers from a population of 126 farmers were selected through simple random sampling. Primary data were collected through questionnaires and interviews, while secondary data were obtained from official agricultural and statistical sources. Data were analyzed using total cost, total revenue, farm income, and Revenue Cost Ratio (RCR) calculations. The results show that average production was 2,256 kg of harvested dry grain per hectare with an average selling price of IDR 4,100 per kg. Total revenue reached IDR 9,249,600 per hectare, production costs IDR 5,285,749 per hectare, and income IDR 3,963,851 per hectare per growing season. The RCR value of 1.75 indicates that farming is financially feasible. Nevertheless, the monthly income equivalent remains low, so feasibility based on RCR has not fully reflected adequate farmer household welfare. Productivity improvement, cost efficiency, water management, adaptive varieties, and market access strengthening are required.